Biogas initiative from municipal solid waste in northern Thailand - Det Damrongsak; Chatchawan Chaichana (Energy Reports, 2020)
Biogas systems from solid waste landfill and their pipeline network have been constructed with a total biogas capacity of 1000~m3/day in two villages in Bantan subdistrict in northern Thailand. Two hundred households in two villages receive the benefits from biogas technology in many ways. It requires 217 m3/day of biogas to cover amounts of 100 kg/day of LPG that has been previously used. The heat energy cost is decreased from previously paid of 400 baht/month (12 USD/month) on LPG down to 100 baht/month (3 USD/month) with the existence of biogas as a cooking fuel. Biogas not only is used as energy source for cooking, but also contributes to the reduction of environmental pollutions produced by municipal solid waste. It helps in reducing methane (CH4) release to atmosphere by 400~kg equivalent to 10,000~kg CO2. Local communities gain new knowledge in biogas technology and its benefits. Major success to the biogas program comes from the collaboration between the solid waste disposal center, households, and government department. Biogas energy surely offers an alternative source of heat energy for households and agricultural applications.
Keywords: 330; Biogas; Renewable energy; Cooking fuel; Solid waste